Biting Density and Distribution of Aedes albopictus during the September 2014 Outbreak of Dengue Fever in Yoyogi Park and the Vicinity of Tokyo Metropolis, Japan - Yoshio Tsuda; Yoshihide Maekawa; Kohei Ogawa; Kentaro Itokawa; Osamu Komagata; Toshinori Sasaki; Haruhiko Isawa; Takashi Tomita; Kyoko Sawabe (2015)
A total of 160 autochthonous dengue cases transmitted by Aedes albopictus were reported between August and October of 2014 in Tokyo Metropolis, Japan. Ae. albopictus is a medically important vector of dengue virus, which has expanded its geographic distribution in temperate regions. Understanding the distribution and biting density of Ae. albopictus during the 2014 dengue outbreak in Tokyo is important to evaluate the epidemic risks of dengue fever in other highly populated cities in Europe and Asia. Of the 160 patients, 134 visited the same park (Yoyogi Park) located in central Tokyo. Mosquitoes infected with dengue virus were collected from this park, suggesting that it was the exclusive location for the transmission of dengue. This study aimed to collect referential data to estimate the transmission threshold of dengue virus in terms of biting density of Ae. albopictus and determined high transmission risk areas of dengue virus in Yoyogi Park and its vicinity. The overall mean density of biting Ae. albopictus (7.13/man/8 min) was sufficiently high for successful transmission of dengue virus, and areas with biting densities higher than the overall mean density were classified as high risk areas for the transmission of dengue virus in Yoyogi Park.